The use of some fluorescent stains for studying morphogenesis of micromycetes - Frank, V (Folia microbiologica, 1991)
The use of some classical fluorochromes and optical brighteners in the fluorescence microscopy of micromycetes was investigated. Of the 16 compounds tested on slide cultures of Trichoderma viride 3 were too toxic, whereas the other stained primarily hyphae with various intensity. Reproductive structures did not stain or stained only weakly. With respect to vital staining the optical brightener Blankophor RKH exhibited most favorable properties. It did not inhibit either the growth or sporulation and stained intensively hyphae, septa and growth apices in particular. It also induced intensive fluorescence of a growing yeast culture.
Keywords: Saccharomyces cerevisiae; Fluorescent Dyes; mykologie; Trichoderma; fluorescenční barviva; Mycology